The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1128/jvi.74.22.10508-10513.2000
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycan Sulfation Requirements for Respiratory Syncytial Virus Infection

Abstract: Glycosaminoglycans (GAGs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
246
1
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(255 citation statements)
references
References 45 publications
6
246
1
2
Order By: Relevance
“…To address whether localization of the hRSV N at the cell surface requires active viral replication, we used a recombinant hRSV A2 strain encoding the green fluorescent protein (hRSV GFP ). Because GFP translation from the viral genome is regulated by the hRSV large RNA-dependent RNA polymerase, GFP synthesis serves as reporter for viral replication (17,30). Also, because the GFP displays a half-life of 26 h (31), accumulation of GFP over time [and the increase in its mean fluorescence intensity (MFI)] serves to track the progression of the viral replication cycle in infected cells.…”
Section: Resultsmentioning
confidence: 99%
“…To address whether localization of the hRSV N at the cell surface requires active viral replication, we used a recombinant hRSV A2 strain encoding the green fluorescent protein (hRSV GFP ). Because GFP translation from the viral genome is regulated by the hRSV large RNA-dependent RNA polymerase, GFP synthesis serves as reporter for viral replication (17,30). Also, because the GFP displays a half-life of 26 h (31), accumulation of GFP over time [and the increase in its mean fluorescence intensity (MFI)] serves to track the progression of the viral replication cycle in infected cells.…”
Section: Resultsmentioning
confidence: 99%
“…The RSV attachment glycoprotein has been found to be dispensable for infection of cultured cells by RSV (58 -60); syncytium formation occurs with cells expressing the RSV fusion glycoprotein alone (61,62), and the RSV fusion glycoprotein appears to be able to mediate attachment via glycosaminoglycan interaction (26,58,60,63). However, recombinant HRSV passages 10 -20 times more efficiently in cell culture when both the G and fusion glycoproteins are present compared with when only the fusion glycoprotein is expressed (59).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which this mucin-like extramembranous domain mediates attachment of RSV to host cells or between infected and noninfected host cells is unknown (22). Glycosaminoglycans of cellular proteoglycans have been implicated in RSV attachment (23)(24)(25)(26)(27), but the identities of these proteoglycans or of other cellular receptors are unknown (22,27).…”
mentioning
confidence: 99%
“…The binding of RSV to host cells is facilitated by the presence of cellular glycosaminoglycans (GAGs), particularly heparan sulfate or other iduronic-acid-containing sugar chains (21,29,34). Feldman et al showed that both G and F can bind to immobilized heparin and that soluble GAGs can inhibit the binding and replication of both wild-type RSV and the coldpassaged isolate cp-52, which lacks the G and SH glycoproteins (16).…”
mentioning
confidence: 99%